2020
DOI: 10.3892/ijmm.2020.4569
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopamine functions as a suppressor of benign prostatic hyperplasia by inhibiting epithelial and stromal cell proliferation via suppression of the Hedgehog signaling pathway

Abstract: Stromal-epithelial interaction serves a pivotal role in normal prostate growth, as well as the onset of benign prostatic hyperplasia (BPH). The present study aimed to explore the role of cyclopamine in the proliferation and apoptosis of epithelial and stromal cells in rats with BPH by blocking the Hedgehog signaling pathway. cyclopamine (an inhibitor of the Hedgehog signaling pathway) was administered in a rat model of BPH, and the expression of Ki67 (proliferation factor) was determined by immunohistochemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
8
0
1
Order By: Relevance
“…Recently, Yuan and colleagues had reported that CYC administration suppressed BPH by inhibiting epithelial and stromal cell proliferation 39 . In their study, only primary cultured rat prostate cells and rat models were used.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Yuan and colleagues had reported that CYC administration suppressed BPH by inhibiting epithelial and stromal cell proliferation 39 . In their study, only primary cultured rat prostate cells and rat models were used.…”
Section: Discussionmentioning
confidence: 99%
“…In the results of GO enrichment analysis, we found that up-regulated DEGs were signi cantly enriched in redox, which was consistent with previous studies that the redox system was associated with the development of BPH 43 , and that GO terms enriched in down-regulated DEGs were associated with ion transport 44 , whereas up down-regulated DEGs were enriched in hormonal regulation, and previous studies had demonstrated the involvement of both androgens and estrogens in the progression of BPH 45,46 . In addition, the results of KEGG analysis suggested that the most signi cant pathway was small molecules, which had been shown in previous studies to in uence cell cycle, apoptosis, proliferation, and proliferation [47][48][49] , whereas the up-regulated DEGs were most signi cantly enriched in pathways associated with IGFs and IGFBPs, which have been previously shown to be associated with BPH 50,51 , and inhibition of IGF-1 secretion inhibited the proliferation of prostate epithelial cells 52 , and up-and down-regulated DEGs were also predominantly co-enriched in small molecule compound-related pathways, suggesting that this pathway might play an important role in steroid hormones-induced BPH. To further explore steroid hormonesinduced genomic differences in mice, we used GSEA and GSVA.…”
Section: Discussionmentioning
confidence: 68%
“…As observed in other studies, the Hedgehog agonist purmorphamine was more efficient in inducing osteoblast differentiation at a concentration of 2 μM [ 14 , 15 , 55 ]. The Hedgehog antagonist cyclopamine inhibited the osteoblast differentiation and because the concentration of 1000 nM seems to induce some toxicity specifically based on its effect on Opn gene expression and ALP activity, we selected 10 nM as it was more efficient than 100 nM in inhibiting osteoblast differentiation [ 56 , 57 , 58 ]. In agreement with previous studies, the Notch antagonist DAPT at the concentration of 20 µM was more osteogenic [ 33 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%